2018
DOI: 10.3389/fnbeh.2018.00135
|View full text |Cite
|
Sign up to set email alerts
|

Is Environmental Enrichment Ready for Clinical Application in Human Post-stroke Rehabilitation?

Abstract: Environmental enrichment (EE) has been widely used as a means to enhance brain plasticity mechanisms (e.g., increased dendritic branching, synaptogenesis, etc.) and improve behavioral function in both normal and brain-damaged animals. In spite of the demonstrated efficacy of EE for enhancing brain plasticity, it has largely remained a laboratory phenomenon with little translation to the clinical setting. Impediments to the implementation of enrichment as an intervention for human stroke rehabilitation and a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
107
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 171 publications
(266 reference statements)
3
107
0
1
Order By: Relevance
“…Until recently, an enriched environment remained largely a laboratory phenomenon with little translation to the clinical setting. In animals, an enriched environment proved to be a robust intervention for fostering brain plasticity and recovery from various types of brain injury, including stroke 61. This latter research showed that the ideal enriched environment encourages socialization, exercise, sensory and cognitive stimulation, and task-specific exercise.…”
Section: Therapy Timementioning
confidence: 91%
“…Until recently, an enriched environment remained largely a laboratory phenomenon with little translation to the clinical setting. In animals, an enriched environment proved to be a robust intervention for fostering brain plasticity and recovery from various types of brain injury, including stroke 61. This latter research showed that the ideal enriched environment encourages socialization, exercise, sensory and cognitive stimulation, and task-specific exercise.…”
Section: Therapy Timementioning
confidence: 91%
“…In addition, relevant studies in the systematic review and meta-analysis studies were also included after reading the full-text of the published article. Key terms were adapted from studies that aimed to increase participation in physical activity and rehabilitation exercises through changing the environment (McDonald, Hayward, Rosbergen, Jeffers, & Corbett, 2018).…”
Section: Literature Search Strategymentioning
confidence: 99%
“…Despite substantial evidence demonstrating EE's beneficial effects in animals, few studies have been conducted in humans 16 . There are a number of issues to consider when adapting these interventions for humans.…”
mentioning
confidence: 99%
“…In many studies, a control environment is where animals are reared in simple cages with only the necessary bedding, food and water available 19 . However, this can be seen as a state of impoverishment, with enrichment being closer to the normal state for wild animals 16 . Therefore, the provision of EE actually normalises the typical living condition and rescues the deficits caused by impoverishment.…”
mentioning
confidence: 99%
See 1 more Smart Citation